Batang bayang river flood modeling based on rain return period - Mardizal, Jonni; Arbi, Yaumal; Akmal, Ikhsanul (Jurnal Pendidikan Teknologi Kejuruan, 2023)
West Pasaman Regency is one of the regencies in West Sumatra that experiences flooding the most. In 2020, in April and September, floods occurred in the West Pasaman district, more precisely around the Nagari Ujung Gading area, Lembah Melintang District. Floods most often inundate the Jorong Lombok and Jorong Irian areas. The flood that occurred was caused by the overflow of the Batang Bayang river. Puddles of water inundated at least 150 residents' houses until the water level reached a height of 1 meter. The problem of flooding almost every year is felt by residents who live near the location of the Batang Bayang river. This study aims to determine the flood discharge of the Batang Bayang river with return periods of 2, 5, 10 and 25 years. Then this study also aims to determine the ability of the Bayang Bayang River to flow flood discharge for 2, 5, 10 and 25 years return periods. The results show that the 2-year return period produces a maximum flood discharge of 47.2 m/s3. In the 5-year return period it produces a flood discharge of 110 m/s3, in the 10-year return period it produces a flood discharge of 143.6 m/s3 and at the return period of 25 years resulted in a flood discharge of 189.2 m3/s. The cross section modeling in the 2 year return period resulted in a water elevation of 21.07 meters. The 5-year return period modeling results in a water level elevation of 22.4 meters. The 10-year return period models the water at an elevation of 23.01 meters and the 25-year return period produces a water level of 23.72 meters.